1980
DOI: 10.1002/ana.410070205
|View full text |Cite
|
Sign up to set email alerts
|

Intraventricular hemorrhage in the high‐risk preterm infant: Incidence and outcome

Abstract: To determine the incidence of subependymal (SEH) or intraventricular hemorrhage (IVH) and its short-term outcome, infants of less than 35 weeks' gestation who required intensive care were evaluated and computerized tomographic scans obtained. If the scans showed blood, serial scans were followed until the hemorrhage had resolved and ventricle size was stable. Hemorrhage was quantitated; Seventy-seven of 191 (40.3%) infants were shown to have SEH, IVH, or both; 22 of them (28%) died, and hemorrhage was thought … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
0
1

Year Published

1981
1981
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(51 citation statements)
references
References 18 publications
2
48
0
1
Order By: Relevance
“…Associated events in the pathogenesis of prenatal intracranial hemorrhage are unknown and can only be suspected from studies performed in the neonatal period [15]. Sudden changes in the cerebral blood pressure may cause hemorrhage in the fragile capillaries of the subependymal germinal matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Associated events in the pathogenesis of prenatal intracranial hemorrhage are unknown and can only be suspected from studies performed in the neonatal period [15]. Sudden changes in the cerebral blood pressure may cause hemorrhage in the fragile capillaries of the subependymal germinal matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Most investigators have found an incidence of hemorrhage of approximately 40% in this population, with subsequent posthemorrhagic ventricular dilatation in 25-50% of the infants [1][2][3][4], As ventricular dilatation may result in further brain injury, some form of therapeutic intervention may be indicated in order to prevent progres sive hydrocephalus, as well as preserve neurological integrity. The tradi tional therapy for progressive ventricular dilatation has been surgical placement of a ventriculo-peritoneal shunt.…”
mentioning
confidence: 99%
“…Though incidence of PCH/IVH may be declining, 5,10 prospective studies have consistently reported a 40% to 50% of incidence of IVH in infants weighing 1500 g or less at birth. 3,4,11 At KKUH over a 4-year period, the incidence of PVH/IVH in infants under 35 weeks of gestation at birth was 20.9%, but rose to 40.6% in infants born at or before 30 weeks of gestation. Our incidence of 40.8% of PVH/IVH in infants weighing 1500 g or less is comparable to that reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Our incidence of 40.8% of PVH/IVH in infants weighing 1500 g or less is comparable to that reported in the literature. 3,4,10,11 It is understandable that the incidence of PVH/IVH should be higher in infants under 30 weeks of gestation because of the peculiarity of the blood supply and cerebrovascular physiology at this age. 12,13 Much of the bleeding arises from the germinal matrix.…”
Section: Discussionmentioning
confidence: 99%